A study on the relationship between certain socio-demographic characteristics of female parents and their fertility - Colada, Lex Anthony Cris
This study deals with the relationship between fertility and certain socio-demographic characteristics of women especially those living in Brgy. San Jose, Janiuay. It seeks to accomplish the following objectives: (1) To find out if there is a relationship between age at marriage of women and their fertility (2) To find out if there is a relationship between educational attainment of women and their fertility. (3) To find out if there is a relationship between employment status and their fertility., In the study, it was found that the socio-demographic characteristics of female parents namely age at marriage, educational attainment and employment status affect their fertility. These characteristics, as revealed in the study influence fertility, whether it is for the growth or reduction of fertility.